Pride and prodigies : - Orchard, Andy (Brewer, 1995)
Monsters and the monstrous, whether from the remote pagan past or the new world of Christian Latin learning, haunted the Anglo-Saxon imagination in a variety of ways. In this series of detailed studies, Dr Orchard demonstrates the changing range of Anglo-Saxon attitudes towards the monstrous by reconsidering the monsters of Beowulf against the background of early medieval and patristic teratology and with reference to specific Anglo-Saxon texts. The immediate manuscript context of the monsters in Beowulf is analysed, shedding light on the poet's treatment of the theme of the monstrous and its integration into his work, and a series of parallel discussions consider a range of medieval treatments of the same theme in a variety of analogous texts (all provided with translation), in Latin, Old English, Middle Irish, and Old Icelandic The twin themes of pride and prodigies are suggested by tracing changing attitudes towards the concept of pride and establishing a close link between the proud pagan warriors depicted in Christian tradition and the monsters they fight, and with whom they become increasingly identified
Keywords: Beowulf (anoniem); Epen; Helden (personen); Manuscrits anglais (vieil anglais); Monsters; Monstres - Dans la littérature; Oudengels; Poésie épique anglaise (vieil anglais) - Histoire et critique; Christentum; Religion; Christianity and literature; Epic poetry; English (Old); Heroes in literature; Manuscripts; English (Old); Monsters in literature; Pride in literature; Ungeheuer; Handschrift; Stolz